A cross-sectional study of anxiety, stress, perception and mental health towards online learning of school children in India during COVID-19. Issue 2 (17th February 2021) - Harjule, Priyanka; Rahman, Azizur; Agarwal, Basant
Abstract: The unprecedented outbreak of coronavirus disease has been spread across the world, affecting the lifestyle of the people. It has significantly changed the way of global education and the teaching-learning process. The aim of this study is to provide a broad insight into the awareness characteristics, attitudes and perceived mental health of the school children and their parents towards online learning in India during 2019-nCoV pandemic. The results of this cross-sectional study showed that there is a significant difference between the preferred modes of learning online or traditional classroom methods during the pandemic. A significant increase in the screen times of school children was observed while learning online under school closure scenario. This was one of the causes of several anxiety issues and mental health concerns amongst school going children and their parents in India. It was also observed that there was not much change in the sleeping patterns of the school going children under lockdown situations and most parents were content that their wards are safely learning at home. A composite anxiety index (CAI) of the school going children was developed using some original variables related to anxiety. Statistical findings of newly constructed CAI showed significant relationship with variables related to attitude of school children, sleeping patterns of sleeping children and mental health of parents.